2008
DOI: 10.1634/stemcells.2007-1028
|View full text |Cite
|
Sign up to set email alerts
|

Immune Properties of Human Umbilical Cord Wharton's Jelly-Derived Cells

Abstract: Cells isolated from Wharton's jelly, referred to as umbilical cord matrix stromal (UCMS) cells, adhere to a tissue-culture plastic substrate, express mesenchymal stromal cell (MSC) surface markers, self-renew, and are multipotent (differentiate into bone, fat, cartilage, etc.) in vitro. These properties support the notion that UCMS cells are a member of the MSC family. Here, the immune properties of UCMS cells are characterized in vitro. The overall hypothesis is that UCMS cells possess immune properties that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
425
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 537 publications
(450 citation statements)
references
References 67 publications
20
425
1
4
Order By: Relevance
“…These results were in agreement with Li et al, [24]. The differences between adult-derived MSCs and UC-MSCs are that UC-MSCs have the potential for faster expansion ex vivo, and UC-MSCs have telomerase activity and the umbilical cord is relatively enriched for CFU-F compared with bone marrow [26].…”
Section: Discussionsupporting
confidence: 91%
“…These results were in agreement with Li et al, [24]. The differences between adult-derived MSCs and UC-MSCs are that UC-MSCs have the potential for faster expansion ex vivo, and UC-MSCs have telomerase activity and the umbilical cord is relatively enriched for CFU-F compared with bone marrow [26].…”
Section: Discussionsupporting
confidence: 91%
“…This also means that Modulatists are a heterogenous MSC population that exhibits properties of both UCMSCs and Wharton's jelly-derived MSCs (WJMSCs). As suggested in some previous studies, both UCMSCs and WJMSCs are great prototypes of MSCs with strong immune modulation and low immunogenicity (Barcia et al, 2015;Li et al, 2014;Weiss et al, 2008). Barcia et al (2015) demonstrated that UCMSCs were less immunogenic and showed higher immunosuppressive activity than BMMSCs (Barcia et al, 2015).…”
Section: Discussionmentioning
confidence: 90%
“…In fact, Barcia et al showed that UCMSCs, compared to BMMSCs, show decreased expression of HLA-DRA, HO-1, IGFBP-1, -4 and -6, ILR1, IL6R, and PTGES; however, they show increased expression of CD200, CD273, CD274, IL1B, IL-8, LIF and TGFB2 (Barcia et al, 2015). WJMSCs are also a great source of MSCs; several previous publications have shown that WJMSCs exert strong suppression on lymphocyte proliferation and have low immunogenicity (Weiss et al, 2008;Zhou et al, 2011). In a recent study by , the immune modulation of 4 cell populations (BMMSCs, ADSCs, placenta-derived MSCs and WJMSCs) were compared .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they display immune-privilege properties (52)(53)(54)(55), have been shown to be well tolerated in allogeneic transplantation experiments (56,57), and can be differentiated into cells of mesodermal origin such as bone, cartilage, and adipose tissue (58). Moreover, hUC-MSCs cultured in neural induction medium develop neural morphologies and express neural markers such as Nestin, glial fibrillary acidic protein, and NeuN (5,46,59,60), suggesting that they have great potential for cell-based therapies in the context of central nervous system diseases.…”
Section: Isolation and Expansion Of Huc-mscsmentioning
confidence: 99%